Digital Literacy as a Transformative Framework for Character Education: A Case Study in Madrasah Ibtidaiyah - Mohd Faeez Ilias; Rudi Hartono; Burhanuddin Burhanuddin; Nanda Saputra; Barsihanor Barsihanor; Putra, Purniadi (Universitas Pesantren Kh abdul Chalim Mojokerto, 2026)
Digital transformation has significantly changed learning practices in Islamic primary education; however, the role of digital literacy as a transformative framework for character education, particularly through collaboration between teachers and parents in Madrasah Ibtidaiyah, remains under-explored. To address this research gap, this study investigates how digital media facilitates the internalisation of core moral values, strengthens participatory character building, and enhances students’ ethical reasoning within the Islamic educational context. The research employs a qualitative case study Design, complemented by descriptive quantitative data to ensure triangulation and robust interpretation of findings. Data were collected through systematic classroom observations, in-depth interviews with the madrasah principal, teachers, and students, and digital documentation of learning activities. Qualitative data were analysed using NVivo for thematic coding and pattern validation, while quantitative data were examined using mean score calculations to support the qualitative insights. The findings indicate that digital media effectively enhance students’ understanding of moral values, promote emotional engagement, and provide opportunities for reflective moral reasoning. Teachers demonstrate strong competence in integrating technology into learning, yet parental involvement remains moderate due to constraints in digital literacy and accessibility. Based on these findings, this study proposes a digital literacy-based character education model grounded in transformative and sociocultural learning perspectives. The model provides practical guidance for developing collaborative, technology-integrated character education policies and offers strategies for strengthening teacher-parent partnerships. Ultimately, the study contributes to advancing character education in Islamic primary schools by bridging theoretical, technological, and sociocultural dimensions of moral learning.